Evaluasi Kerusakan Perkerasan Jalan Perkotaan Berdasarkan Metode Pavement Condition Index (PCI) (Studi Kasus: Ruas Jalan Malikul Adil, Kota Langsa) - Ari Juanda; Muammar, Rajib; Sabilla, Arissa (Universitas Iskandar Muda, 2025)
Reliable road infrastructure is a vital component for regional connectivity; however, pavement distress on Malikul Adil Street, Langsa City, has emerged as a critical issue that disrupts local transportation efficiency. This study aims to systematically identify existing distress types and quantitatively assess the pavement condition. The study employed a visual survey method using the Pavement Condition Index (PCI) in accordance with the ASTM D6433 standard to provide an objective evaluation. Data were collected by observing and measuring the type, severity, and quantity of distress such as cracking, distortion, and disintegration on sample units along the road section. The analysis yielded an average PCI score of 16.8. According to standard rating scales, this score classifies the road's condition as 'very poor', indicating severe and widespread structural damage that compromises both the safety and comfort of its users. Potholes and raveling were identified as the most dominant distress types, with severity levels ranging from medium to high (M-H). These findings provide a comprehensive and measurable overview of the pavement's actual condition. Practically, this study provides a valid empirical basis for policymakers to establish priorities and devise more effective, efficient, and targeted highway maintenance programs.